Measuring the Impact of Career Development Services in Canada: Current and Preferred Practices - Lalande, Vivian; Magnusson, Kris (Canadian Journal of Counselling and Psychotherapy, 2008)
There is a lack of knowledge regarding the value and impact of career development services, particularly in Canada. The goals of this research were to better understand career development services’ evaluation practices and the value of these practices fromthe perspectives of Canadian agencies, practitioners, policy makers, and employers. Data were collected using a survey, focus groups, and telephone interviews. Differences were found between the type and size of career service providers regarding the importance andpractice of career development evaluation. Overall, practitioners, agencies, policy makers, and employers agreed that it was important to evaluate career development services; however, there is a great need to improve how and what is being measured. Implicationsfor future research and evaluation practices are considered.